Molecular confirmation of candidate Hsp70 gene associated with heat tolerance in BC3F2 advanced backcross lines and their phenotypic resemblance with recurrent chilli Kulai - Usman, Magaji G.; Rafii, Mohd Yusop; Yusuff, Oladosu; Mohammad Yusoff, Martini; Ismail, Mohd R.; Ridzuan, Raihana (Taylor & Francis, 2020)
Domestic production of chilli in Malaysia is insufficient which accounted for 52% self-sufficiency level. Poor performance of local varieties under high temperatures above 42°C is one of the major factors affecting chilli production. This study was conducted with the objective of introgress heat-tolerant gene (Hsps) from AVPP0702 donor into Kulai using marker-assisted backcrossing. A total of 68 SSR markers, including Hsp linked markers that showed polymorphism between the parents were used to assess the generation of backcrossing; BC1F1, BC2F1, BC3F1 and BC3F2 and the average RPG percentage of the recurrent parent was found to be 81, 90, 95 and 97%, respectively. The pattern of Hsp expression in the backcross generations was similar to the donor parent (upregulated with more than 4-fold increase). Twelve improved heat tolerant chilli lines were developed. Most of the morphological and agronomical traits were recovered in the selected improved heat-tolerant genotypes from Kulai such as plant height, number of days to 50% flowering, number of fruits, fruit length and total fruit yield per plant. Improved high-yielding heat-tolerant chilli lines showed tolerance to high temperature as well as did not express any negative effect on agronomic traits in comparison with Kulai variety.